2006
DOI: 10.1111/j.1467-2979.2006.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing regime shifts in the marine environment

Abstract: Recent years have seen a plethora of studies reporting that ‘regime shifts’ have occurred in the North Atlantic and Pacific Oceans during the last century. In many cases, the criteria used to distinguish a regime shift have not been explicitly stated. In other cases, a formal definition has been proposed and the data set assessed against it. Developing a universal quantitative definition for identifying and distinguishing between purported climatic and ecological regime shifts has proved problematic as many au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 76 publications
(265 reference statements)
2
124
1
Order By: Relevance
“…This observation corroborates existing results by Azumaya and Ishida (2000) and . It further matches temporal patterns in zooplankton biomass in the North Pacific, which decreased to the lowest level on record in 1989 and remained low at least until 1997 (Lees et al, 2006), and also coincides with the increase in chum salmon population size during the last quarter of the 20 th century (Kaeriyama and Katsuyama, 2001). …”
Section: Maturation Schedule and Growthsupporting
confidence: 72%
See 1 more Smart Citation
“…This observation corroborates existing results by Azumaya and Ishida (2000) and . It further matches temporal patterns in zooplankton biomass in the North Pacific, which decreased to the lowest level on record in 1989 and remained low at least until 1997 (Lees et al, 2006), and also coincides with the increase in chum salmon population size during the last quarter of the 20 th century (Kaeriyama and Katsuyama, 2001). …”
Section: Maturation Schedule and Growthsupporting
confidence: 72%
“…Evidence supporting the importance of the environment in driving maturation trends in Pacific salmon comes mostly from the response of salmon populations to recent changes in oceanographic regimes (Hare and Mantua, 2000;King, 2005;Lees et al, 2006;Overland et al, 2008). Despite ongoing controversy, it is commonly assumed that since the mid-twentieth century, the North Pacific has experienced regimes shifts in 1976-77, in the winter of 1988-89 (Beamish et al, 1999;Hare and Mantua, 2000;King, 2005), and in 1998 (McFarlane et al, 2000;King, 2005;Overland et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The general scientific literature contains a bewildering diversity of methods that in a widest sense correspond to change-point detection, either in time or space (Box 3). In this review we contend that terms like regime shift [10,14] (Box 4) or the combination of different climatic indices related to Pacific fisheries into a single one [28].…”
Section: Detecting Thresholds and Regime Shifts In Ecological Datamentioning
confidence: 99%
“…The general scientific literature contains a bewildering diversity of methods that in a widest sense correspond to change-point detection, either in time or space (Box 3). In this review we contend that terms like regime shift [10,14] principle would be very relevant for detecting regime shift mechanisms related to bistability and hysteresis loops. Unfortunately, it has also been shown that this approach [34] is prone to false positives, as it is reported to find multimodality even in data sets generated from a multivariate normal distribution [35], which, by definition, cannot be MULTIMODAL.…”
mentioning
confidence: 99%
“…Often the ecosystem response to these multiple pressures is nonlinear, which may lead to unexpected behavior by the ecological system (deYoung et al 2008) and to sudden, ecosystem-wide shifts, i.e., regime shifts (Francis et al 1998, Lees et al 2006, Beaugrand et al 2008, Kirby et al 2009, Alheit and Bakun 2010. There is little doubt that, in the future, the pressure on marine systems may increase due to acceleration of climate-induced changes thatsynergistically to other human and natural processes-affect the ecosystem dynamics, with major consequences for the provision of ecosystem services (Philippart et al 2011).…”
Section: Introductionmentioning
confidence: 99%